A Randomized Case-controlled Clinical Trial of the Effect of Preemptive Etoricoxib, Prednisolone and a Control Group on of Postoperative Sequelae after Surgical Removal of Impacted Mandibular Third Molars (Medico Legal Update, 2021)
Background: The aim of this study was to compare the anti-inflammatory effects of prednisolone andetoricoxib after third molar extraction.Method: A prospective, controlled study was conducted on 39 volunteers were allocated in three differentgroups, to receive either 120 mg etoricoxib or 10mg prednisolone 30 minutes prior to the procedure, and alsoa controlled group who didn’t receive any medication pre-operatively.Baseline measurements were obtainedpreoperatively, and subsequent assessments were made on immediate postoperative, at 48 hours and 7 daysafter surgery to measure postoperative facial swelling by use of linear measurements, interincisal mouthopening width and visual analog scale score for pain. The amount of analgesics consumed was recorded.Descriptive statistics were used to compare the two groups at P < 0.05.Conclusion: Considering the results that were obtained upon the efficacy of different pre-emptive medication,Etoricoxib showed statistically significant values in terms of pain reduction and restriction in mouth opening,in the other hand prednisolone showed significance results in terms of edema reduction.